Correlation between right-to-left shunt and sudden sensorineural hearing loss: protocol for a case–control study - Cong Liu; Jun Hu; Jianrong Zheng; Ying Zhan; Yajing Cheng; Bihua Lu; Weiqiang Yang (BMJ Open, 2023)
Background and purpose Sudden sensorineural hearing loss (SSNHL) is a neurological and otolaryngological emergency during which rapid diagnosis and early treatment are of great importance. Clinical experience indicates that a considerable number of patients with SSNHL have concurrent right-to-left shunt (RLS). With limited reports, the association between SSNHL and RLS is yet unclear and there is a need for large observational studies to explore their latent relationship.Methods and analysis This proposed study is a prospective, observational case–control study. A total of 194 eligible participants matched in age and sex will be divided equally into two groups: 97 patients with SSNHL included in the case group and 97 individuals without SSNHL in the control group. Medical evaluations, including clinical characteristics, laboratory examination, audiological examination and ultrasonography examination, will be performed in all subjects. The primary outcome of the study is the difference in RLS rates between the groups. Differences in patent foramen ovale rates and other measured variables will be further assessed. A conditional logistic regression as a correlation analysis will be used to evaluate the relationship between RLS and SSNHL.Discussion This study may provide evidence on the correlation between RLS and SSNHL in order to enrich the aetiology of SSNHL.Ethics and dissemination The study protocol has been approved by the Ethics Committee of Peking University Shenzhen Hospital. A written informed consent form will be signed and dated by the participants and the researchers before the study begins. The results will be disseminated in peer-reviewed publications.Trial registration number ChiCTR2200064067.